2020
DOI: 10.1080/03639045.2020.1788067
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state interaction of ibuprofen with magnesium stearate and product characterization thereof

Abstract: Figure S1. 2950 -2920 cm -1 IR spectral region (SNV normalized) colored according to the MgS content (a) and stress conditions (b) Figure S2. VIP plot of the DSC curves PLS model (a), DSC curves colored according to the MgS content (b) and stress conditions (c)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Surprisingly, FH, FI and FJ showed the highest solubility of IBF (247.2–252.8 µg/mL) among all formulations due to the presence of 2.5% MgSt. While MgSt disperses in basic conditions (PBS, pH 7.4) at a certain temperature and humidity, MgO from the MgSt reacts with carboxyl acid group from IBF, which might cause an acid–base reaction to form magnesium salt of ibuprofen [ 39 ]. This result significantly increased the drug solubility (at 24 h of mixing), which could be attributed to the improvement of the drug particle dispersion which helps in drug solubilization [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, FH, FI and FJ showed the highest solubility of IBF (247.2–252.8 µg/mL) among all formulations due to the presence of 2.5% MgSt. While MgSt disperses in basic conditions (PBS, pH 7.4) at a certain temperature and humidity, MgO from the MgSt reacts with carboxyl acid group from IBF, which might cause an acid–base reaction to form magnesium salt of ibuprofen [ 39 ]. This result significantly increased the drug solubility (at 24 h of mixing), which could be attributed to the improvement of the drug particle dispersion which helps in drug solubilization [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…While MgSt is dispersed in basic conditions such as PBS, faster release or increase in the drug solubility at 24 h could be attributed to improvements in the drug particle dispersion which helped in solubilizing the drug [ 40 ]. MgSt might play an important role in enhancing the solubility and dissolution of IBF particles by forming a complex mixture of the drug, such as the Mg salt of IBF that dissociates in the solvent and improves the solubilization [ 39 ]. Additionally, faster drug release could be due to the presence of both excipients which reduced the particle–particle cohesion and increased the drug–solvent interactions, thus enhancing the solubility of IBF.…”
Section: Resultsmentioning
confidence: 99%
“…This approach can be used to characterize the thermodynamic properties of the solid phase and screen for intermolecular interactions between two solids. 16 A binary phase diagram was constructed using DSC thermal analysis. The endothermic peaks for FA, NIC, and an FA-NIC binary mixture in various molar ratios were determined using a DSC apparatus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…starch paste) that can be contaminated if stored prior to utilization in production (22). Several studies have indicated incompatibilities between IBU and boundary lubricants, in terms of identified changes in crystallinity and formation of eutectic mixtures of IBU and excipients such as stearic acid and magnesium stearate (23)(24). Traditionally, IBU tablets are sugar (sucrose) coated in order to mask their unpleasant taste, as well as due to the acidity of IBU.…”
Section: Solid Dosage Formsmentioning
confidence: 99%